Effects of FTY720 on Lung Injury Induced by Hindlimb Ischemia Reperfusion in Rats - Wang, Liangrong; Chen, Feifei; Pan, Yafei; Lin, Lina; Xiong, Xiangqing (Mediators of Inflammation, 2017)
Background. Sphingosine-1-phosphate (S1P) is a biologically active lysophospholipid mediator involved in modulating inflammatory process. We investigated the effects of FTY720, a structural analogue of S1P after phosphorylation, on lung injury induced by hindlimb ischemia reperfusion (IR) in rats. Methods. Fifty Sprague-Dawley rats were divided into groups SM, IR, F3, F5, and F10. Group SM received sham operation, and bilateral hindlimb IR was established in group IR. The rats in groups F3, F5, and F10 were pretreated with 3, 5, and 10 mg/kg/d FTY720 for 7 days before IR. S1P lyase (S1PL), sphingosine kinase (SphK) 1, and SphK2 mRNA expressions, wet/dry weight (W/D), and polymorphonuclear/alveolus (P/A) in lung tissues were detected, and the lung injury score was evaluated. Results. W/D, P/A, and mRNA expressions of S1PL, SphK1, and SphK2 were higher in group IR than in group SM, while these were decreased in both groups F5 and F10 as compared to IR (p<0.05). The lung tissue presented severe lesions in group IR, which were attenuated in groups F5 and F10 with lower lung injury scores than in group IR (p<0.05). Conclusions. FTY720 pretreatment could attenuate lung injury induced by hindlimb IR by modulating S1P metabolism and decreasing pulmonary neutrophil infiltration.